Music and Art in School Social Work with Socially Isolated and Marginalized Students: A Participatory Action Research Enhancing the Educational Inclusion During COVID-19. - Styliani Farmaki; Agapi Kandylaki (International Journal of School Social Work, 2025)
This article presents and discusses a Participatory Action Research (PAR) project, which was conducted shortly after the outbreak of COVID-19 (March 2020) by the first author (researcher) in collaboration with thirteen School Social Workers (SSWs) (co-researchers-interveners), 11 from Greece and two from Cyprus. The SSWs performed an original “quarantine video-song” composed by the researcher and dedicated to all students, entitled “We’ve Not Forgotten You”. They promoted it publicly and used it as a tool in 15 tailor-made, arts-based, brief, systemic interventions to help enhance the educational inclusion of students who faced intense social isolation and marginalization challenges. The main findings on how educational inclusion was enhanced are illustrated hereby by three indicative case studies, i.e. one migrant student, one student with chronic illness and disability, and a “whole school of Roma students”. Music and art were linked to the students’ interests and pandemic-related issues and offered them opportunities to strengthen their “voices” regarding the emerging challenges. Depending on the case, the interventions’ focus expanded from the individual and family level to the classroom, school, and community level. The interventions contributed to self-expression, empowerment, highlighting of strengths, and coping with transitions. They also enhanced the sense of school belonging and recognition, promoted interdisciplinary and inter-school collaborations, and strengthened the school-family-community relation. The SSWs, as co-researchers and members of a group coordinated by the researcher, exchanged feedback, and reflected collectively on the interventions, coming up with proposals for future action to enrich school social work practice during COVID-19 and beyond.
Keywords: school social work; participatory action research; music- and arts-based systemic interventions; social isolation and marginalization; educational inclusion; COVID-19